Global optimization approach for the H2-norm model reduction problem - Assuncao, Edvaldo [UNESP]; Peres, Pedro L D [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
A branch and bound algorithm is proposed to solve the H2-norm model reduction problem for continuous-time linear systems, with conditions assuring convergence to the global optimum in finite time. The lower and upper bounds used in the optimization procedure are obtained through Linear Matrix Inequalities formulations. Examples illustrate the results.
Keywords: Algorithms; Control system synthesis; Linear systems; Mathematical models; Matrix algebra; Optimization; Polynomials; State space methods; Continuous time linear systems; Linear matrix inequalities; Optimal control systems